Safety and immunogenicity of GamEvac-Combi, a heterologous rVSV- and rAd5-vectored Ebola vaccine: a randomized controlled multicenter clinical trial in the Republic of Guinea and Russia - Logunov, Denis Y.; Dolzhikova, Inna V.; Boiro, Mamadou Y.; Kovyrshina, Anna V.; Dzharullaeva, Alina S.; Erokhova, Alina S.; Grousova, Daria M.; Tukhvatulin, Amir I.; Izhaeva, Fatima M.; Simakova, Yana V.; Ordzhonikidze, Maria K.; Lubenets, Nadezhda L.; et al. (Frontiers in Immunology, 2025)
BackgroundEbola virus disease (EVD) is one of the most dangerous and lethal diseases affecting humans. There are several licensed vaccines against EVD, but it remains one of the priority diseases for research and development of effective vaccines.MethodsA double-blind randomized placebo-controlled trial was performed to evaluate safety and immunogenicity of rVSV- and rAd5-vectored vaccine GamEvac-Combi in healthy adults of both sexes between 18 and 60 years. Safety and immunogenicity were assessed during the observation period of 12 months. Immunogenicity was assessed with GP-specific ELISA, IFN-γ ELISA, and plaque pseudoneutralization assay.ResultsVaccinated participants showed marked GP-specific IFN-γ response at day 28 and neutralizing response at day 42 (GMT = 32.6, seroconversion rate 96.3%). GP-specific IgG antibody levels in vaccinated participants peaked at day 42 (GMT = 9345) and persisted for a year after vaccination (GMT = 650).ConclusionThe vaccine showed favorable safety profile and induced robust cell-mediated immune response and strong humoral immune response that lasts at least for a year from the start of vaccination.Clinical trial registrationClinicalTrials.gov, identifier NCT03072030; Pan African Clinical Trial Registry, identifier PACTR201702002053400.